ANALISIS KINERJA KEUANGAN PERUSAHAAN SEMEN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Pradana, Arga Yenu (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out and to examine the financial performance of cement companies which go public in the Indonesia Stock Exchange. Either quantitative or qualitative analysis is applied in this research as the analysis technique which is performed by conducting calculation on liquidity, profitability, leverage and activity of PT. Semen Gresik (Persero) Tbk, PT. Indocement Tunggal Prakasa Tbk dan PT. Holcim Indonesia Tbk which are listed in the Indonesia Stock Exchange. Excellent company among the three PT cement is PT Semen Gresik (Persero), Tbk as the average ratio analysis of liquidity, solvency, activity, and profitability highest results, but never exceed the guideline limits except ratio unless the liquidity ratio and even then still say good according to the ratioKeywords: Liquidity Rasio, Aktivity, Provitability, Solvability, Grow and Financial Performance